Pediatric Residency Training in Türkiye - Müjgan Alikaşifoğlu (Çocuk Dergisi)
In our country, the Ministry of Health is involved in the regulation and licensure of postgraduate medical education. The Turkish Medical Association plays a role in specialist training through the Coordination Board of Specialist Associations. There are two big associations that are members of the Turkish Medical Association (The Turkish Pediatric Association, The Turkish National Pediatric Association). Modern medical education in the Ottoman Empire started on 14 March 1827. The first Turkish book on newborn care and diseases was written in 1844. Lectures by a pediatrician, at the Military Medical School began in the 1900s. With the law, which was enacted on 8 November 1928 in the Republican period, a requirement of licensure in pediatrics was determined as a two-year working period. With the 1933 university reform, the İstanbul University Medical Faculty Department of Pediatrics was established. Today, Pediatrics residency training continues to be given in 62 Medical Faculties and 29 Training and Research Hospitals, according to the quota data for the 2023 Medical Specialization Examination. In 1995, the Turkish Pediatric Association and the Turkish National Pediatric Association came together and decided to work on improving Pediatric Education in Turkey. On September 14, 2003, the General Assembly of the Turkish Pediatrics Board convened for the first time. In 2019, the board of pediatrics accelerated its work with a new perspective. In 2020, the Pediatric board started accreditation of educational programs and in 2021, two levels (Knowledge and skill exams) the National board exam.